Cultural influences on interpersonal communication among a different gender of KUPTM KL students - Aida Suhana Abdul Hamid; Aida Zuliyana Ahmad Anuar (Human Sustainability Procedia, 2022)
The influences of culture are affected by history, geography, traits and changes through the process. It’s perceived by individuals differently, especially by a different gender. However, good communication skills are crucial to survive in a different environment, especially in a higher education institution. A different environment, geography and culture required a very high level of communication skills to avoid misunderstanding or any communication risk. The study aimed to describe the relationship between different gender cultural influences and interpersonal communication among KUPTM KL students. Quantitative methods were applied in the study, and a set of questionnaires was distributed among 160 students of KUPTM KL. In addition, the result showed a significant relationship between cultural influences and interpersonal communication of KUPTM KL students, while gender differences do not affect cultural influences and interpersonal communication. It also shows the level of cultural influences and interpersonal communication of the respondents. Hence, the study contributes to the field of communication through the establishment of more comprehensive variables related to participation in interpersonal communication and helps in extending the Social Penetration Theory in most of the stages includes.